MOLECULAR ASPECTS OF PLANT VIRUS MOVEMENT THROUGH PLANTS - Deryabina, N.D.; Gritsenko , D.A.; Galiakparov , N.N. (Eurasian Journal of Applied Biotechnology, 2017)
The movement of viruses through plants plays a key role in viral infection spread and establishment of the virus. Viruses have developed many strategies to ensure their efficient spread through plants and within cells to promote protein expression, replication, and production of the next generation. The movement of viruses is mainly mediated by movement proteins (MP) and to a lesser extent by capsid proteins (CP). Short-distance movement is promoted by the interactions of MP and/or CP with the host cellular cytoskeleton, which directs targeting of viral particles to the plasmodesmata. Plasmodesmata allow free intercellular passage of small molecules and limit movement of viruses due to their exclusion size. Viruses use different strategies to expand the diameter of the plasmodesmataand to enable spread of infectious viral particles over short distances. Viruses have also adapted to interact with particular host factors to promote their long-distance movements through carbohydrate fluxes. Different viral species interact with various host factors to promote their movement. The main plant regulators of viral movement along plants are callose deposits and the RNA interference mechanism. The study of viral movement is important for agriculture, for medicine, and for vector engineering to obtain recombinant products.